Korelasi Fungsi Kepala Sekolah Sebagai EducatorDengan Kompetensi Pedagogik Guru SMA Darussalam Blokagung Tegalsari Banyuwangi - Moh. Mahmud; Sugiyono Sugiyono; Fitriyana Fitriyana (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2020)
The objectives of this study were: (1) to determine the function of the principal as an educator at SMA Darussalam Blokagung Banyuwangi, (2) to determine the pedagogical competence of SMA Darussalam Blokagung Banyuwangi teachers, (3) to determine the relationship between the principal's function as an educator and the pedagogical competence of SMA teachers. Darussalam Blokagung Banyuwangi. This study used a quantitative descriptive method with product moment correlation analysis on data validity testing and to find data reliability using the alpha formula, while for data analysis tests used qualitative analysis for questions 1 and 2 and used quantitative analysis for question number 3. The population of this study was all 43 SMA Darussalam Blokagung Tegalsari teachers in Banyuwangi. Observation data collection techniques, questionnaires and documentation. The results found that: (1) the function of the principal as an educator in SMA Darussalam Blokagung Banyuwangi was 92% which means that it has a Very Good category. (2) the pedagogical competence of teachers at SMA Darussalam Blokagung Banyuwangi is 91%, which means it is in the Very Good category. (3) The relationship between the principal's function as an educator and the pedagogical competence of SMA Darussalam Blokagung Banyuwangi teachers is 0.599 with a percentage of 59.9% which falls into the Enough category.